2019
DOI: 10.32718/nvlvet9410
|View full text |Cite
|
Sign up to set email alerts
|

Study of toxicness of snails meat on biological model

Abstract: Snails can be found in any part of the planet. They belong to the class of gastropods, which includes terrestrial, freshwater, marine snails. Their ancestors are some of the most ancient species of the fauna. Archaeologists say that the first lived on our planet 500 million years ago. There are about 90000 species of snails, but only 3 species have gained worldwide fame: gigantic African snail, grape and Helix аspersa. Snail's meat improves bowel function and normalizes metabolism. It is believed that due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…In agreement with the other studies, Danilova [53] found that fresh meat of H. aspersa maxima, H. aspersa Müller, and H. pomatia appeared non-toxic, and that the mice remained healthy throughout the experiment. Kouachi et al [42] found that at a concentration of 160 mg, rats showed the best weight gain, and the behavior of all animals remained normal.…”
Section: Acute Toxicitysupporting
confidence: 91%
“…In agreement with the other studies, Danilova [53] found that fresh meat of H. aspersa maxima, H. aspersa Müller, and H. pomatia appeared non-toxic, and that the mice remained healthy throughout the experiment. Kouachi et al [42] found that at a concentration of 160 mg, rats showed the best weight gain, and the behavior of all animals remained normal.…”
Section: Acute Toxicitysupporting
confidence: 91%
“…У хімічний склад равлика входить велика кількість вітамінів і мінеральних елементів: тіамін, піридоксин, рибофлавін, кобаламін, фолієва кислота -одним словом, практично всі вітаміни групи В, а також вітамін К, РР, Е і ретинол, за змістом якого равлики є практично рекордсменами. Слиз равликів використовують у косметології [11].…”
unclassified